2019
DOI: 10.1055/a-0998-4079
|View full text |Cite
|
Sign up to set email alerts
|

Visfatin Levels May be an Early Marker of Atherosclerosis in Patients with Acromegaly

Abstract: The purpose of the study was to compare serum visfatin levels between patients with acromegaly and healthy controls and to evaluate the relationships between visfatin levels and epicardial fat thickness (EFT), carotid intima media thickness (cIMT), and ankle brachial index (ABI). We conducted a cross-sectional case-control study of 54 patients with acromegaly (37 females and 17 males) and 34 healthy controls (22 females and 12 males). Serum visfatin was measured by ELISA. Acromegalic and control participants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
1
0
1
Order By: Relevance
“…Researchers have also demonstrated that visfatin can increase matrix metalloproteinases (MMPs) expression, promoting collagen degradation and elevating the plaque vulnerability index [22]. Overexpression of visfatin has been observed in smooth muscle cells and foam cells, contributing to the instability of atherosclerotic plaques in acute myocardial infarction patients [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have also demonstrated that visfatin can increase matrix metalloproteinases (MMPs) expression, promoting collagen degradation and elevating the plaque vulnerability index [22]. Overexpression of visfatin has been observed in smooth muscle cells and foam cells, contributing to the instability of atherosclerotic plaques in acute myocardial infarction patients [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Açlık plazma glukozu kontrol grubuna göre daha yüksek saptandı(p=0,426). Biyokimyasal olarak çeşitli çalışmalarda visfatin, irisin, ürotensin-III gibi testler çalışılmış ve akromegalide kardiyovasküler risk faktörlerinin belirlenmesi amaçlanmıştır [8][9][10] . Yeni çalışmalar aterosklerozun risk faktörleri arasında EYK ve KIMK göstermektedir.…”
Section: Karotis İntima-media öLçümüunclassified